Thermally-induced phase transformations in KNNS-BNKZ lead-free piezoceramics. Issue 3 (March 2020) - Tangsritrakul, J.; Tang, C.C.; Day, S.J.; Hall, D.A.
Abstract: Promising piezoelectric properties have been reported in potassium sodium niobate-based ceramics by introducing Bi0.5 (Na0.82 K0.18 )0.5 ZrO3 (BNKZ) into K0.48 Na0.52 Nb0.95 Sb0.05 O3 (KNNS) solid solutions in order to control the polymorphic phase transformation temperatures. In the present study, synchrotron x-ray powder diffraction (SXPD) was employed in combination with dielectric and ferroelectric measurements in order to clarify the influence of BNKZ on the phase transition temperatures of (1-x)KNNS-(x)BNKZ ceramics (with x = 0 to 0.05). The results, presented in terms of temperature-dependent SXPD patterns, dielectric permittivity and thermal depolarisation characteristics, confirmed that polymorphic phase transformation temperatures all shifted in a systematic manner with increasing BNKZ content. Broadening of the phase transition regions was also observed with increasing BNKZ content, leading to improvements in thermal stability of the ferroelectric properties. Microstructural examination of the KNNS-BNKZ ceramics revealed the presence of core-shell microstructures; this was correlated with the presence of weak shoulders on the diffraction peaks.